Simplified Modeling and Experimental Validation of a Combi-Storage Distribution Tank for Seasonal Thermal Energy Storage Systems - Tryfon C. Roumpedakis; Aris-Dimitrios Leontaritis; Prokopios Vlachogiannis; Efstratios Varvagiannis; Antonios Charalampidis; Sotirios Karellas (Thermo, 2023)
This study regards the evaluation of the performance of a thermally stratified tank as an intermediate combi-storage tank for a solar-driven residential thermal system coupled to a seasonal energy storage system. In such applications, the efficient operation of this intermediate tank is crucial to the enhanced exploitation of the harvested solar energy and the minimization of heat losses. In this perspective, the development of a dedicated model in TRNSYS software and its validation with experimental results are investigated. With respect to the simulation model’s discretization, it was found that beyond 60 nodes, the benefits to the model’s accuracy are almost negligible. Comparing the experimental data with the simulation’s results, the predicted temperature profile converges accurately to the measured values under steady-state conditions (threshold stabilization period of 1000 s after charging/discharging has occurred). However, the response of the model deviates considerably under transient conditions due to the lack of detailed inertia modeling of both the tank and the rest of the system components. Conclusively, the developed 1D simulation model is adequate for on- and off-design models where transient phenomena are of reduced importance, whereas for dynamic and semi-dynamic simulations, more detailed models are needed.